l-DOPA and Freezing of Gait in Parkinson’s Disease: Objective Assessment through a Wearable Wireless System - Suppa, Antonio; Kita, Ardian; Leodori, Giorgio; Zampogna, Alessandro; Nicolini, Ettore; Lorenzi, Paolo; Rao, Rosario; Irrera, Fernanda (Frontiers in Neurology, 2017)
Freezing of gait (FOG) is a leading cause of falls and fractures in Parkinson’s disease (PD). The episodic and rather unpredictable occurrence of FOG, coupled with the variable response to L-Dopa of this gait disorder, makes the objective evaluation of FOG severity a major clinical challenge in the therapeutic management of patients with PD. The aim of this study was to examine and compare gait, clinically and objectively, in patients with PD, with and without FOG, by means of a new wearable system. We also assessed the effect of L-Dopa on FOG severity and specific spatio-temporal gait parameters in patients with and without FOG. To this purpose, we recruited 28 patients with FOG, 16 patients without FOG and 16 healthy subjects. In all participants, gait was evaluated clinically by video-recordings and objectively by means of the wearable wireless system, during a modified 3-m Timed Up and Go (TUG) test. All patients performed the modified TUG test under and not under dopaminergic therapy (ON and OFF therapy). By comparing instrumental data with the clinical identification of FOG based on off-line video-recordings, we also assessed the performance of the wearable system to detect FOG automatically in terms of sensitivity, specificity, positive and negative predictive values, and finally accuracy. TUG duration was longer in patients than in controls and the amount of gait abnormalities was prominent patients with FOG compared with those without FOG. L-Dopa improved gait significantly in patients with PD and particularly in patients with FOG mainly by reducing FOG duration and increasing specific spatio-temporal gait parameters. Finally, the overall wireless system performance in automatic FOG detection was characterized by excellent sensitivity (93.41%), specificity (98.51%), positive predictive value (89.55 %), negative predictive value (97.31 %), and finally accuracy (98.51%). Our study overall provides new information on the beneficial effect of L-Dopa on FOG severity and specific spatio-temporal gait parameters as objectively measured by a wearable sensory system. The algorithm here reported potentially opens to objective long-time sensing of FOG episodes in patients with PD.